Applications of Optical Coherence Tomography in Pediatric Clinical Neuroscience - Avery, Robert A.; Rajjoub, Raneem D.; Trimboli-Heidler, Carmelina; Waldman, Amy T. (Neuropediatrics, 2015)
For nearly two centuries, the ophthalmoscope has permitted examination of the retina and optic nerve—the only axons directly visualized by the physician. The retinal ganglion cells project their axons, which travel along the innermost retina to form the optic nerve, marking the beginning of the anterior visual pathway. Both the structure and function of the visual pathway are essential components of the neurologic examination as it can be involved in numerous acquired, congenital and genetic central nervous system conditions. The development of optical coherence tomography now permits the pediatric neuroscientist to visualize and quantify the optic nerve and retinal layers with unprecedented resolution. As optical coherence tomography becomes more accessible and integrated into research and clinical care, the pediatric neuroscientist may have the opportunity to utilize and/or interpret results from this device. This review describes the basic technical features of optical coherence tomography and highlights its potential clinical and research applications in pediatric clinical neuroscience including optic nerve swelling, optic neuritis, tumors of the visual pathway, vigabatrin toxicity, nystagmus, and neurodegenerative conditions.
Keywords: optical coherence tomography; optic neuritis; papilledema; optic pathway gliomas